Zinc-Catalyzed Synthesis of Dithioacetals through Double Hydrosulfenylation of Alkynes by Thiols - Taniguchi, Nobukazu; Kitayama, Kenji (Synlett, 2018)
Zinc-catalyzed hydrosulfenylation of alkenes can be performed in various solvents, and the corresponding products are obtained regioselectively. Dihydrosulfenylation of alkynes with thiols can also be achieved by using a zinc catalyst, and the reaction is preferentially promoted over monohydrosulfenylation. The reaction can also give dithioacetals regioselectively in excellent yields.
Keywords: hydrosulfenylation; dihydrosulfenylation; dithioacetals; zinc catalysis; alkynes; alkenes